A comprehensive comparative economic analysis of ACO and CS technique for optimal operation of stand-alone HES - Lakshmi E S.; Singh S.P. (My University, 2025)
In a hybrid energy system, there are generally more than three sources of generation to meet the given load, optimization technique optimally schedules the generation of these resources such that a given objective is met. There are many such methods to optimize a system to achieve desired results. This paper gives a comprehensive comparative economic analysis of ant colony optimization and cuckoo search technique to achieve optimal operation of hybrid stand-alone system. For the analysis, hybrid energy system having solar photovoltaic generator and wind turbines with energy storage system backed by diesel generators is used to power a remote village with no access to grid power. The comparative analysis of the two optimization methods with objective to achieve lowest per unit cost of generation is discussed. © Springer Nature Singapore Pte Ltd 2020.